Increased intraocular inflammation in retinal vein occlusion is independent of circulating immune mediators and is involved in retinal oedema - Zhou, Yufan; Qi, Jinyan; Liu, Hengwei; Liang, Shengnan; Guo, Tingting; Chen, Juan; Pan, Wei; Tan, Huanhuan; Wang, Jie; Xu, Heping; Chen, Zhongping (Frontiers in Neuroscience, 2023)
We aim to understand the link between systemic and intraocular levels of inflammatory mediators in treatment-naïve retinal vein occlusion (RVO) patients, and the relationship between inflammatory mediators and retinal pathologies. Twenty inflammatory mediators were measured in this study, including IL-17E, Flt-3 L, IL-3, IL-8, IL-33, MIP-3β, MIP-1α, GRO β, PD-L1, CD40L, IFN-β, G-CSF, Granzyme B, TRAIL, EGF, PDGF-AA, PDGF-AB/BB, TGF-α, VEGF, and FGFβ. RVO patients had significantly higher levels of Flt-3 L, IL-8, MIP-3β, GROβ, and VEGF, but lower levels of EGF in the aqueous humor than cataract controls. The levels of Flt-3 L, IL-3, IL-33, MIP-1α, PD-L1, CD40 L, G-CSF, TRAIL, PDGF-AB/BB, TGF-α, and VEGF were significantly higher in CRVO than in BRVO. KEGG pathway enrichment revealed that these mediators affected the PI3K-Akt, Ras, MAPK, and Jak/STAT signaling pathways. Protein–Protein Interaction (PPI) analysis showed that VEGF is the upstream cytokine that influences IL-8, G-CSF, and IL-33 in RVO. In the plasma, the level of GROβ was lower in RVO than in controls and no alterations were observed in other mediators. Retinal thickness [including central retinal thickness (CRT) and inner limiting membrane to inner plexiform layer (ILM-IPL)] positively correlated with the intraocular levels of Flt-3 L, IL-33, GROβ, PD-L1, G-CSF, and TGF-α. The size of the foveal avascular zone positively correlated with systemic factors, including the plasma levels of IL-17E, IL-33, INF-β, GROβ, Granzyme B, and FGFβ and circulating high/low-density lipids and total cholesterols. Our results suggest that intraocular inflammation in RVO is driven primarily by local factors but not circulating immune mediators. Intraocular inflammation may promote macular oedema through the PI3K-Akt, Ras, MAPK, and Jak/STAT signaling pathways in RVO. Systemic factors, including cytokines and lipid levels may be involved in retinal microvascular remodeling.